Clinical diagnosis and treatment of alpha-fetoprotein-negative small hepatic lesions - Xu, Yiyao (AME Publishing Company, 2013)
OBJECTIVE: We examined 103 cases over the last five years and discussed diagnosis and treatment of alpha-fetoprotein (AFP)-negative small hepatic lesions. Background: Small hepatic lesions (less than 2 cm in diameter) usually have no typical imaging characteristics and therefore are difficult to diagnose, especially when AFP tests provide a negative result. METHODS: A total of 103 patients with AFP-negative small hepatic lesions from January 2003 to December 2008 were retrospectively reviewed. Differential diagnosis was performed by digital subtraction angiography (DSA), dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI), contrast-enhanced ultrasound (CEUS), or positron emission tomography-computed tomography (PET-CT) based on the multiplicity of lesions. Ninety-four patients with suspected cancers underwent partial hepatectomy. Clinical data were collected from hospital records and follow-up questionnaires. RESULTS: Hepatocellular carcinoma (HCC) diagnostic sensitivity of DSA, DCE-MRI, CEUS and PET-CT was 88.2%, 93.9%, 88.9% and 88.9%, respectively. The surgery-related complication rate was 6.4%. Prognosis was good, with 1- and 3-year survival rates of 98.8% and 76.1%, respectively. CONCLUSIONS: DSA, DCE-MRI, CEUS and PET-CT are valuable for diagnosis of small hepatic lesions. Partial hepatectomy is a preferred surgical procedure. Surgery for small liver cancers usually has little risk and good prognosis, therefore it can be actively applied in suspected HCC cases.